L’entreprise patrimoniale de Louis-Joseph Guyot (1836-1924) à Dourdan, entre érudition et médiation - Léda Martines (Les Cahiers de l'École du Louvre)
In 1863 Louis-Joseph Guyot inherited the medieval Château de Dourdan in the Essonne department: he made it his holiday home then progressively the object of his investigations and whims and the place where he applied his research. Aware that the built heritage of which he was the trustee was of public interest, Louis-Joseph Guyot devoted himself to the promotion and conservation of the Dourdan past. He was one of the local, private actors, working in the shadow of official institutions, whose name has not gone down in history; and yet his work was far from insignificant. This article comprehends the logic of his undertaking and also aims to communicate the scope of an individual action that was part of the growing awareness of cultural heritage in the nineteenth century.